Historical Dictionary of the Arab-Israeli Conflict - Kumaraswamy, P. R. (Historical dictionaries of war, revolution, and civil unrest (Unnumbered), 2015)
"Competing Jewish and Arab national claims over the Holy Land form the core of the Arab--Israeli conflict, thereby transforming it into the most intensely-fought struggles in the history of humanity. The conflict evokes unparalleled passion and hostility not only among its immediate participants and neighbors but also in the wider international community. The involvement of three principal monotheistic religions makes the conflict a truly universal contestation. As a result, it often contributes to bouts of violence, turmoil and terrorism in the Middle East and beyond. This second edition of Historical Dictionary of the Arab-Israeli Conflict covers the history through a chronology, an introductory essay, appendixes, and an extensive bibliography. The dictionary section has over 600 cross-referenced entries important events, key personalities, official positions of principal states and the UN and other efforts to find a peaceful settlement. This book is an excellent access point for students, researchers, and anyone wanting to know more about this conflict."--Back cover